5G millimeter wave UE test method and analysis - Jian GONG; Yu ZHANG (Dianxin kexue)
In the 5G millimeter wave UE OTA RF conformance test, EIRP and TRP type of tests are important OTA items.Currently, this method relying on 3GPP-defined random scan to lock the beam to determine the maximum EIRP and TRP, but this method is time-consuming and lacks accuracy.A non-signaling test method was proposed, which could not only achieve more accurate measurements compared with the current EIRP and TRP test methods but also make it possible to use the non-directional OTA site as the measurement environment, further reducing the test cost and time cost, and increasing the flexibility of the test environment selection.